Labor Market Flexibility as an Adjustment Mechanism in Economy of Poland (Economic and Political Thought, 2013)
High unemployment rate is a problem observed not only in Poland butalso in most European Union countries. Because of that, the issue of adjustingmechanisms of the labor market and methods of decreasing the unemploymentrate seem to be very important, especially when the mechanismsfail. The article discusses the functioning of adjusting mechanisms in conditionsof flexible and inflexible remuneration. It also analyses, on the basisof the theory and examples of contemporary economies, why the adjustingmechanisms fail on the labor market. Next, with the use of Eurostat data andsimple analysis of the regression, the article presents an assessment of thelabor market in Poland. Finally, the article includes conclusions on directionsof addressing the unemployment problem in Poland, focusing on structuralfactors.